VISUALISASI 3D JAM GADANG BUKITTINGGI DENGAN KONSEP VIRTUAL REALITY BERBASIS ANDROID - Syukri, Hamdan; Ikhwan, Ali; Alda, Muhamad (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2024)
The research is titled "Implementation of 3D Visualization on the Tourist Attraction of Jam Gadang Bukittinggi with Android-Based Virtual Reality Concept." The main issue addressed in this study is the physical limitation faced by visitors who seek to understand the spatial conditions and information about the Jam Gadang building, resulting in suboptimal services. Consequently, visitors to Jam Gadang must obtain a special permit from the Tourism Office of Bukittinggi to access and ascend the building to its summit. Therefore, an Android-based Virtual Reality application is needed to allow users to comprehend the spatial conditions and information by virtually entering and ascending the Jam Gadang building without the need to be physically present. Information will be presented in the form of panels within the virtual environment, accompanied by a narrated voice.